Crambe grain drying: Evaluation of a linear and double resistance driving force model and energetic performance. (December 2017) - Cruz, Fernanda Paola Butarelli; Johann, Gracielle; de Oliveira, Kamila Cavalcante; Palú, Fernando; da Silva, Edson Antonio; Guirardello, Reginaldo; Curvelo Pereira, Nehemias
Abstract: In this study, a review of the main industrial applications of crambe grains, as well as the modeling of drying kinetics applying the double resistance and the linear driving force model are presented. Fixed bed drying characteristics of crambe grains were investigated in a convective drier, on the drying air conditions at temperatures of 40, 50 and 60 °C and 1.5, 2.0 and 2.6 m s −1 . The drying kinetics was phenomenologically modelled, for such, the main hypotheses adopted were the double resistance and the linear driving force model for water diffusion inside the grains. Centesimal composition of the grains was calculated, in order to determine their thermophysical properties. The mass transfer inner coefficient was considered as a linear function of the humidity of the bed. The theoretical mathematical model suggested, the linear approximation of the mass transfer inner coefficient, and the empirical model for the heat transfer convective coefficient resulted in a relative mean error of 7.79%. The specific energy consumption values ranged from 12.45 to 5.98 MJ kg −1, respectively for drying conducted at 40 °C and 2.5 m s −1 and at 60 °C and 1.5 m s −1 .